Estudo da reatividade cruzada em amostras de soro de cães positivos para Leishmania sp., Babesia canis e Ehrlichia canis, pelo ensaio imunoenzimático indireto e pela reação de imunofluorescência indireta - Oliveira, Trícia Maria F de Sousa [UNESP]; Furuta, Patrícia I [UNESP]; Carvalho, Débora de; Machado, Rosangela Z [UNESP] (FapUNIFESP (SciELO), 2008)
To verify the presence of cross-reaction among leishmaniosis, ehrlichiosis and babesiosis in serological diagnostics used in human visceral leishmaniasis control programs, serum samples from leishmaniasis endemic and non-endemic areas were collected and tested by Indirect Fluorescent Antibody (IFAT) and Enzyme-linked immunosorbent assay (ELISA). All serum samples from endemic areas were positive for Leishmania sp., by ELISA and IFAT, 51% positive for Babesia canis and 43% for Ehrlichia canis by IFAT. None of the serum samples from non-endemic areas were positive for Leishmania sp., by IFAT, but 67% were positive for B. canis and 78% for E. canis using the same test. When tested by ELISA for Leishmania sp., four samples from non-endemic area were positive. These dogs were then located and no clinical signs, parasites or antibody was detected in new tests for a six month period. Only one of these 4 samples was positive for B. canis by IFAT and ELISA and three for E. canis by IFAT. The results of the work suggest a co-infection in the endemic area and no serological cross-reaction among these parasites by IFAT and ELISA.
A study of cross-reactivity in serum samples from dogs positive for Leishmania sp., Babesia canis and Ehrlichia canis in enzyme-linked immunosorbent assay and indirect fluorescent antibody test.
Keywords: bacterium antibody; protozoon antibody; animal; Babesia; blood; cross reaction; dog; Ehrlichia canis; enzyme linked immunosorbent assay; fluorescent antibody technique; immunology; Leishmania; Animals; Antibodies, Bacterial; Antibodies, Protozoan; Cross Reactions; Dogs; Enzyme-Linked Immunosorbent Assay; Fluorescent Antibody Technique, Indirect